Analysis of hot research topics on environmental migration - Shang, Yanguang; Liang, Bing; Shi, Guoqing; Sun, Zhonggen; Hua, Yinjie; Ye, Taotao; Lu, Zhongman (Frontiers in Environmental Science, 2024)
Global environmental issues have become one of the most prominent risk issues in society, and it is of great theoretical and practical importance to study the intrinsic correlation between environmental change and population migration.Based on the Web of Science core ensemble database (WOS) and National Knowledge Infrastructure database (CNKI) sources, CiteSpace visual bibliometric software was used to construct a map of research hotspots in the field of environmental migration. The specific research methods included word frequency analysis, cluster analysis, and burst word detection analysis. The study found that the research hotspots of environmental migration mainly include:migration caused by environmental pollution;migration caused by the construction of environmental protection projects;migration caused by environmental protection activities; migration caused by environmental degradation; migration caused by climate change;migration caused by environmental disasters; andmigration caused by environmental improvement activities. our new insights into the relationship between environmental factors and migration include:nonlinear relationships, multi-dimensional vulnerability,livelihood diversification,local context and agency, feedback loops and feedback effects.For future research directions on environmental migration, we can start from the following aspects ： (1)Multidisciplinary Approaches;(2)Longitudinal Studies;(3)Regional and Localized Studies;(4)Climate Change Projections;(5)Policy Impact Analysis;(6)Migration and Urbanization;(7) Social and Cultural Adaptation;(8)Technological and Data Advancements;(9)Ethical Considerations;(10)Community-Based Research.